"Nostalgia as a Cultural Marker in Thomas Pynchon's Gravity's Rainbow&#34 - Grgas, Stipe (1999)
Because he contends that Pynchon's fictional world is based on a recognizable American experience the author reads the motif of nostalgia as an important component of the American conception of history. His presupposition is that his analysis, coming as it does from a culture which is both spatially and temporally distinct from America, enables him to register certain layers of the text which tend to be missed when viewed from within the domicile culture.
Projekt MZOS
ENG